EFEKTIFITAS LEMBAR KERJA MAHASISWA (LKM) STRUKTUR ALJABAR - Yunita, Alfi; Septia, Tika (Jurnal Pelangi : Research of Education and Development, 2014)
Algebra structure is a branch of abstract mathematics, which is generally more difficult than the other more concrete branches of mathematics. The on going problems in the subject of  Algebra structure is the students do not understand about the concept of algebra structures, so that students have difficulty in using theories or theorems in evidence. In addition, another cause is the algebra structure of the teaching material is too abstract, so that students are less motivated to read supporting books and it causes low student activities. There may be one way to improve the motivation, activity and learning outcomes of students like using the Student Worksheet (MFIs). The purpose of this research was to develop an effective MFI Guided on the subject of Algebraic Structures in STKIP PGRI West Sumatra. This type of research was a developmental research. This research used 4-D models composed of 4 phases: definition phase (define), the design (design), development (develop) and spread (disseminate). In the deployment phase of the trial is limited to classes only. Effectiveness was analyzed through the observation student activity during lectures, student motivation by providing motivation questionnaire after using Guided MFI and student outcomes. Data analysis was analyzed descriptively with the results after using Guided MFIs in the subject of Algebra structure can enhance the activity, motivation and learning outcomes of students. The level of student mastery learning outcomes is more than 68%. It means that MFI Guided is effective in improving the student learning outcomes. The results show that the MFIs Guided on the subject of Algebra Structure developed has been effectively used as a teaching material for students.